A near infrared index to assess effects of soil texture and organic carbon content on soil water content. (28th September 2018) - Soltani, I.; Fouad, Y.; Michot, D.; Bréger, P.; Dubois, R.; Cudennec, C.
Summary: Characterization of soil hydrodynamic properties is important for assessing the soil water regime. Ex situ measurements are costly and time consuming. Reflectance spectroscopy can rapidly estimate several soil properties, including soil water content (SWC). Here, we evaluated the ability of visible (vis) and near‐infrared (NIR) spectroscopy to assess the effects of soil texture and soil organic carbon (SOC) content on SWC. Thirteen undisturbed soil surface blocks were sampled in 2014 across the Brittany region, western France. Textural classes ranged from sandy loam to sandy clay loam texture, and SOC content ranged from 8.12 g kg −1 to 62.3 g kg −1 . Aggregates of 3–4‐cm width and 5–6‐cm height were extracted and set at 10 matric potentials from saturation to permanent wilting point (1585 kPa). At given pressure heads, soil samples were scanned in triplicate to acquire reflectance spectra between 350 and 2500 nm. Spectra were converted into continuum removal and we focused on the absorption band near 1920 nm, which is linked to combination vibrations of water. We defined a new index based on the full width at half maximum (FWHM) of the absorption feature near 1920 nm. Results showed a linear relation between this NIR index and the volumetric SWC ( R 2 > 0.9) for every soil aggregate. The slope and the intercept of the line were correlated well with soil texture and SOC content. Results indicated that the parameters of this linear relation offer a new way to study SWC and water retention properties of soils in relation to their physical properties. Highlights: We used vis–NIR spectroscopy to assess effects of texture and SOC content on soil water content. Formulated a new spectral index based on absorption feature of water near 1920 nm. Linear relation between SWC and NIR index; its parameters are related to texture and SOC content. Vis–NIR spectroscopy can be relevant to assess effects of texture and SOC content on SWC.